How and when can economic skills enhance cooperation? - Evelyn Korn; Stephan Meisenzahl; Johannes Ziesecke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
Conventional wisdom has it that economic training and education tends to produce less cooperative people - where cooperation means following group-oriented goals. This issue has attracted particular attention in discussions of the current economic crisis where it was asked if increasing marketization of societies has created an environment encouraging amoral selfish behavior of financial intermediaries and other economic agents. We provide some evidence against this claim with the help of an experiment, using an investment game with a public-goods character. Modest guidance of strategic abilities increases the degree of cooperation if the institutional setting permits reputation building. We thus conclude that economic practice can enhance cooperation in a socially stable environment.
Keywords: 330